Comparison of recommendations in national/regional Guidelines for prevention and control of MRSA in thirteen European countries - Kalenic, Smilja; Cookson, Barry; Gallagher, Rose; Popp, Walter; Asensio-Vegas, Angel; Assadian, Ojan; Blok, Annette; Brusaferro, Silvio; Eastaway, Anne; Elstrom, Petter; Girod Schreinerova, Miroslava; Hartemann, Philippe; et al. (International Journal of Infection Control, 2010)
A comparison of methicillin-resistant Staphylococcus aureus (MRSA) prevention and control recommendations, as stated in national/regional guidelines of 13 European countries was performed based on a structured questionnaire filled by representatives of professional societies or institutions. The aim of this study was to be a source of guidelines, references and views which can inform discussions at national/regional/local levels. Countries were devided in two groups based on proportion of MRSA in blood cultures positive with Staphylococcus aureus retrieved from EARSS 2008: low proportion (4 countries) and higher proportion (9 countries). Guidelines from all respective countries have several common general recommendations: MRSA-positive patients have to have the same care as those that are not carrying MRSA, hand hygiene measures including the use of alcohol hand rubs are identified as important in the prevention of MRSA spread, environmental cleaning and/or disinfection has to be performed routinely, and personal protective equipment has to be used whilst working with MRSA positive patients. Surveillance and screening is also a part of all guidelines. Major differences among low and higher MRSA proportion countries, identified as successful practices, were: have guidelines and update it regularly, have guidelines not only for hospitals, but also for nursing homes and home practice, isolate MRSA positive patients in single room, perform MRSA screening based on risk categories in hospitals and nursing homes, and perform decolonisation of MRSA carriers.